2020
DOI: 10.1177/0963662520977700
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge about the nature of science increases public acceptance of science regardless of identity factors

Abstract: While people’s views about science are related to identity factors (e.g. political orientation) and to knowledge of scientific theories, knowledge about how science works in general also plays an important role. To test this claim, we administered two detailed assessments about the practices of science to a demographically representative sample of the US public ( N = 1500), along with questions about the acceptance of evolution, climate change, and vaccines. Participants’ political and religious views predicte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 34 publications
(51 reference statements)
0
22
0
1
Order By: Relevance
“…Additionally, there has been accumulating evidence that it is the knowledge of how science works and not the access to scientific facts and consensuses that is associated with persuasion and long-lasting behaviour change in polarised contexts. 49 The case for evidence-based communication of science In the past three decades, media studies have established framing as a set of phenomena in which the journalistic coverage reduces some elements of the perceived reality. Then, the coverage arranges the remaining essential items into a coherent narrative that promotes an interpretation anchored on plausibility.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there has been accumulating evidence that it is the knowledge of how science works and not the access to scientific facts and consensuses that is associated with persuasion and long-lasting behaviour change in polarised contexts. 49 The case for evidence-based communication of science In the past three decades, media studies have established framing as a set of phenomena in which the journalistic coverage reduces some elements of the perceived reality. Then, the coverage arranges the remaining essential items into a coherent narrative that promotes an interpretation anchored on plausibility.…”
Section: Discussionmentioning
confidence: 99%
“…Prior work has also suggested that general science knowledge and reasoning skills, understanding of the nature of scientific theories, and accepting good scientific evidence as a criterion for belief all relate positively to acceptance of evolution (Weisberg et al, 2018(Weisberg et al, , 2021. The fact that the Chinese sample has a higher mean score on general science knowledge and reasoning skills, a better understanding of the nature of scientific theories, a higher mean agreement with accepting good scientific evidence as a criterion for belief, and a lower mean agreement with accepting gut feeling as a criterion for belief may also partly explain the higher acceptance level among the Chinese respondents compared with the US sample.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the Pew Research Center experimented with questions about evolution using "humans and other living things" versus "animals and other living things." These surveys found that individuals were much more likely to accept evolution when they were asked about non-human living things, and also that the effect of this slight change in question wording on evolution acceptance varied among different religious populations (Pew Research Center, 2019; see also Weisberg et al, 2021).…”
Section: Acceptance Of Evolutionmentioning
confidence: 99%
“…These different factors illustrate the issue-dependency and high heterogeneity of predictors of the controversiality of a topic [53,54]. However, some factors seem to be general predictors of the acceptance and rejection of scientific knowledge, like conspiracy ideation [55] and knowledge about NOS [56].…”
Section: Figurementioning
confidence: 96%